Acceptability of self-collected vaginal swabs for sexually transmitted infection testing among youth in a community-based setting in Zimbabwe. (July 2023) - Rochford, Helena; Larsson, Leyla; Simms, Victoria; Mavodza, Constancia; Sigwadhi, Lovemore; Dauya, Ethel; Machiha, Anna; Mavhura, Mitchell; Bipiti, Tatenda; Mangena, Chido; Bandason, Tsitsi; Ferrand, Rashida A; et al.
Background: Youth are a high-risk group for sexually transmitted infections (STIs). To increase access to STI testing, convenient approaches for sampling and testing are needed. We assessed the acceptability of self-collected vaginal swabs (SCVS) for STI testing among young women (16–24 years) attending a community-based sexual and reproductive health service in Zimbabwe. Methods: A SCVS was used for point-of-care testing for Trichomonas vaginalis and a urine sample for testing for Chlamydia trachomatis and Neisseria gonorrhoeae . A questionnaire was administered to investigate the acceptability of SCVS versus self-collected urine samples. In-depth interviews (IDIs) explored the experience of SCVS and reasons for sample collection preference. Qualitative analysis was predominantly deductive. Results: We recruited 129 women who took up STI testing (median age 20 years, IQR 18–22 years) and conducted 12 IDIs. Most participants reported that they understood the instructions (93.0%) and found SCVS easy (90.7%). Many participants felt relaxed (93.0%), in control (88.4%) and that they had enough privacy (90.7%). Pain or discomfort were reported by 16.3% and embarrassment by 15.5%. Among the 92 (71.3%) participants who provided both a SCVS and urine sample, 60.9% preferred SCVS. Sample collection method preferences were similar between 16–19 and 20–24year-olds. In IDIs, clear instructions, privacy, trust in the service and same-day results were perceived as important facilitators to taking up SCVS. Participants frequently described feeling relaxed and confident whilst taking a SCVS. Pain and discomfort were uncommon experiences. Conclusions: SCVS for STI testing are acceptable to young women and a feasible method of sample collection in community-based settings.